Estudio de factibilidad para la creación de una empresa de puertas y ventanas de bambú del cantón Quevedo, año 2015 - Cruz Chiriboga, Iván Daniel (2015)
The following research is focused on a feasibility study for the creation of a business development and marketing of doors and windows of bamboo, I investigate market research, technical, economic - financial. In concluding this first part the approval was taken to the positioning of the current market scenarios. The second part of this study the technical analysis on the location of the new company will be located where its infrastructure, the size of the field will have a dimension of 12m wide x 20m long = 240m2 was so determined, based on installed capacity and expected production, machinery and equipment required for the manufacturing process, and organizational issues concerning the distribution of personal. Then the third part of this study in which monetary information that previously settled in the technical study, among others, the initial investment of $ 24,864.00 total operating costs, working capital, was obtained financing is presented 80,44% of the value of the investment will be through a bank loan and the remaining 19.56% is personal contribution of the investor, statements of income; In short this part is tried to obtain all the necessary monetary figures on the economic evaluation. As the final part of this study examined profitability through financial, such as NPV (net present value) which is $ 515,059.19, the IRR (internal rate of return) of 585.98% and a B / C indicators ( cost-benefit) of $ 1.55 this demonstrates the viability of the investment.